2000
DOI: 10.1086/313926
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Prevalence of Maternal Antibody to Measles Virus throughout Infancy: A Review

Abstract: The effectiveness of vaccination against measles, the leading cause of vaccine-preventable deaths in infants globally, is greatly impacted by the level of maternal antibody to measles virus (or "measles maternal antibody"; MMA) during infancy. Variation in the prevalence of maternal antibody to measles virus between infant populations across countries and sociodemographic strata is poorly understood. We reviewed the literature on the prevalence of MMA, focusing on 3 principal determinants: starting level of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 37 publications
11
112
1
3
Order By: Relevance
“…Placental transfer has also been found to be less efficient in infants in developing countries than in industrialized countries (22). Coexisting infections such as malaria and human immunodeficiency virus infections are also associated with decreased levels of maternal antibodies in infants (5,17). These factors should not have complicated the results of the present study, since premature infants and infants whose mothers were not living in metropolitan France at the time of pregnancy were excluded from the study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Placental transfer has also been found to be less efficient in infants in developing countries than in industrialized countries (22). Coexisting infections such as malaria and human immunodeficiency virus infections are also associated with decreased levels of maternal antibodies in infants (5,17). These factors should not have complicated the results of the present study, since premature infants and infants whose mothers were not living in metropolitan France at the time of pregnancy were excluded from the study.…”
Section: Discussionmentioning
confidence: 85%
“…Although the percentage of infants with detectable measles-neutralizing antibody levels remained around 40% for infants 7 to 8 months old, 90% of the infants included in the study had antibody concentrations under 120 mIU/ml after 6 months of age. Studies carried out in other countries have also shown that infants over 6 months of age in a well-immunized population may be poorly protected against measles (5,12,24,32,40,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one-half of the patients had contact history with another measles patient. In developing countries high birth rates and high contact rates combined with early decrease of maternal antibodies result in high incidence of measles, during the first year of life (12,13,14). It was demonstrated that the ratio of children with detectable antibodies declined from 61.4 percent at 22-23 weeks of age to 20 percent at 26-27 weeks of age in Turkey (15).…”
Section: Discussionmentioning
confidence: 99%
“…Placental transfer of IgG provides specific immune protection in infants during the early weeks of life [43]. The benefits are short-lived and only limited protection is conferred [42].…”
Section: Functional Immaturity Of the Infant Immune System And The Pementioning
confidence: 99%